Changes In Family Consumption Patterns Post Covid-19 Pandemic: A Qualitative Study - Moh. Nasrul Muslim; Abdur Rohman (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
The COVID-19 pandemic has brought significant changes to various aspects of life, including family consumption patterns. After the implementation of restrictions and the transition toward a new normal order, society began to show adaptation in consumption habits that differ from pre-pandemic times. This study aims to deeply examine changes in family consumption patterns in the post-pandemic era using a qualitative approach. Data collection was conducted through in-depth interviews with 15 respondents from diverse social and economic backgrounds, supported by observation and document analysis. Findings indicate that digitization is a key factor in transforming consumption patterns, with an increase in the use of online platforms such as shopping apps and telehealth services. In addition, changes in time structure due to work-from-home policies have influenced the frequency and types of goods consumed, especially in fulfilling basic needs. Although some government policies have had a positive impact on purchasing power, their implementation has not been fully effective for all segments of society. The role of social media has also become increasingly prominent in shaping consumption preferences, particularly among younger generations. This study concludes that the changes in consumption patterns after the pandemic are not merely temporary but tend to be part of a new lifestyle that is more selective, efficient, and oriented toward health and technology. Therefore, this research provides an important contribution to understanding the dynamics of household consumption behavior in the new normal era.